(untitled) (Bangladesh Journal of Agricultural Research, 2022)
The study was carried out to evaluate some biorational approaches for the management of two leaf eating cabbage caterpillars (S. litura and P. xylostella) at three planting dates of cabbage. We did not find the population of Pieris brassicae in this study. In the 1st planting, the lowest percent head infestation (3.79%) were recorded in the pheromone mass trap+ Bt+ SNPV treated plot followed by hand picking + pheromone for trapping S. litura and P. xylostella+ spraying Bt (5.79%) and pheromone for trapping S. litura and P. xylostella+ spraying Bt treated plots (6.01%) as against 10.35% infestation in untreated control. Similarly, the lowest percent head infestation were recorded in the pheromone + Bt+ SNPV treated plot from 2nd and 3rd planting dates 10.85% and 16.33%, respectively. P. xylostella larvae was not found at 1st planting. The highest percent reduction of head infestation over control was recorded from pheromone mass trap+ Bt+ SNPV treated plots which were 63.4%, 49.7% and 46.62% respectively at three planting dates. Significantly the highest marketable yield (56.86 t ha-1)) and highest BCR (4.32) was recorded from pheromone + Bt+ SNPV treated plot in three date of planting. Interaction of pheromone mass trap+ Bt+ SNPV and 1st planting of cabbage was proved to be the most effective management approaches against two leaf eating caterpillars of cabbage. The population of leaf eating caterpillar of cabbage at elarly planting was much less. Thus, it does not require too much spraying to suppress leaf eating caterpillar of cabbage at early planting. Bangladesh J. Agril. Res. 45(2): 185-198, June 2020